Profitability in State-Owned Enterprises Banks Listed on the Indonesian Stock Exchange 2019-2023 as an Effect of CAR, TATO, and NPL - Ayu Levia Tryana (eCo-Fin, 2024)
The world of banking plays a crucial role in society and the government. Banks serve as a vital indicator of a country's progress, making them the lifeblood of its economy. As domestic banking becomes more advanced, the competition between banks is intensifying. Just as a financial analyst would recommend, every bank must strive to secure funds and leverage their resources, management, and technology to achieve optimal efficiency and effectiveness in combating competition. This research seeks to analyze the impact of CAR, total asset turn over (TATO), and NPL on profitability (ROA) in state-owned banks listed on the Indonesia Stock Exchange from 2019 to 2023. The data analysis technique in this research utilizes path analysis. Through data collection, a total of 4 state-owned banks were included in this research. These banks have published financial reports for a span of 5 years, resulting in a dataset of 20 data points. The data collected was analyzed using a tool commonly employed by financial analysts to conduct panel data linear regression analysis. According to the research findings, it is evident that CAR has a noteworthy positive impact on Profitability (ROA). Additionally, TATO also has a positive and significant influence on Profitability (ROA). On the other hand, NPL exhibits a negative and significant effect on Profitability (ROA).